1994
DOI: 10.1161/01.hyp.24.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nonselective endothelin antagonist on vascular remodeling in deoxycorticosterone acetate-salt hypertensive rats. Evidence for a role of endothelin in vascular hypertrophy.

Abstract: We have previously shewn that the endothelin content in arteries of deoxycorticosterone acetate (DOCA)-salt hypertensive rats is increased. We designed this study to examine, using the new orally active nonselective endothelin receptor antagonist bosentan, whether this increase in vascular endothelin may contribute to elevated blood pressure and vascular hypertrophy in DOCA-salt hypertensive rats. Rats received bosentan (100 mg/kg body wt per day) for 3 weeks mixed with their food. Systolic blood pressure of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
152
5
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(176 citation statements)
references
References 30 publications
14
152
5
5
Order By: Relevance
“…Hypertrophic remodeling rather than eutrophic remodeling of resistance arteries, seems to occur in models associated with an upregulated ET system suggesting that ET-1 system upregulation leads to vascular hypertrophy. 42 In the current study, we observed no significant change in diameter, media thickness, cross-sectional area of the media, nuclear cell count or media-to-lumen ratio in first-order mesenteric resistance arteries of 32-week-old SHR caused by reducing blood pressure by means of a 4-week treatment with a vasodilator (hydralazine). This means that a decrease in blood pressure alone cannot reverse structural changes in these arteries.…”
Section: Discussioncontrasting
confidence: 62%
“…Hypertrophic remodeling rather than eutrophic remodeling of resistance arteries, seems to occur in models associated with an upregulated ET system suggesting that ET-1 system upregulation leads to vascular hypertrophy. 42 In the current study, we observed no significant change in diameter, media thickness, cross-sectional area of the media, nuclear cell count or media-to-lumen ratio in first-order mesenteric resistance arteries of 32-week-old SHR caused by reducing blood pressure by means of a 4-week treatment with a vasodilator (hydralazine). This means that a decrease in blood pressure alone cannot reverse structural changes in these arteries.…”
Section: Discussioncontrasting
confidence: 62%
“…This observation was not unexpected since endothelin-1 is predominantly released abluminally from endothelial cells, and thus acts primarily as an autocrine/paracrine factor (Wagner et al, 1992). Consistent with this latter premise, plasma endothelin-1 levels were normal in the DOCA-salt hypertensive rat model, albeit the administration of a non-selective ET receptor decreased elevated blood pressure, and ameliorated vascular remodelling (Calderone et al, 1994;Li et al, 1994). In this regard, the potential paracrine role of locally released endothelin-1 on the underlying vasculature of the ovariectomized rat was examined.…”
Section: Discussionmentioning
confidence: 72%
“…55,66,67 These observations were extended by other laboratories and it can now be concluded that endothelin plays more of a vasoconstrictor and hypertrophy-promoting role in saltdependent (eg, DOC-salt, aldosterone-induced, Dahl SS, insulin-resistant, and 1K-1C Goldblatt models), 55,66,[68][69][70] than in salt-independent or renindependent forms of experimental hypertension (eg, SHR, 2K-1C Goldblatt, and L-NAME-induced hypertension). 55,56,67,70 The only exception seems to be the hypertension produced by exogenous administration of angiotensin II, in which endothelin participates in BP maintenance and vascular hypertrophy.…”
Section: Endothelin and Experimental Saltsensitive Hypertensionmentioning
confidence: 90%